The fluid envelope of our planet : how the study of ocean currents became a science - Mills, Eric L., 1936- (University of Toronto Press, 2009)
A detailed and beautifully written account of the history of oceanography, The Fluid Envelope of Our Planet is an engaging account of the emergence of a scientific discipline.